Insects. [electronic resource] - Banks, Nathan, 1868-; Canadian Arctic Expedition (1913-1918) (Ottawa : J. de L. Taché, 1918)
Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 3, pt. B. Includes list of titles in the series. Electronic reproduction. Mode of access: Internet. 44